Group theory with applications in chemical physics - Jacobs, P. W. M. (Patrick W. M.) (Cambridge University Press, 2005)
This book provides a self-contained and rigorous account on the fundamentals and applications of Group Theory and Symmetry to chemical physics. With numerous worked examples, this book will appeal as an introductory guide to advanced undergraduates or beginning graduate students studying physical sciences.